(untitled) (Feni University Journal, 2026)
Advertising induces the purchase situation most likely to be more convincing in dayto- day affairs. Customers gain from in-store advertisements in the purchasing ambiance, regardless of whether they are pre-set to a competitor’s brand. When purchasing, a consumer with a favorable brand image and positive brand beliefs is typically influenced by in-store advertisements to tolerate risk or vulnerability. In many areas, in-store advertisements influence consumer decisions through fashion, design, and salesmanship. Owing to the ideology, this study aimed to determine how in-store advertisements affected customers’ desire or decision to buy in a retail setting. With 410 (random) respondents’ opinions from 40 outlets/one-stop shops in the Dhaka, Chittagong, and Feni districts through confirmatory factor analysis, factors such as in-store advertisements and customers’ purchase decisions, brand selections, attitudes, fashion, design, and salesman’s function were shown to have a discernible influence with each other, based on their respective relationships. Ultimately, this research showed how in-store advertisements affect customers’ exploratory and purchasing decisions in retail. Ultimately, these justifications will represent the new aesthetic and the significance of in-store advertisements for customers’ learning paradigms concerning retail purchases. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (43-62)